Retrofitting a water quality control structure to maximize pollutant removal efficiency for an existing wetland - Trifone, Laurie, author; Roesner, Larry A., advisor; Sharvelle, Sybil, advisor; Laituri, Melinda, committee member (Colorado State University. Libraries, 2014)
An existing seven acre wetland captures stormwater runoff from a 505 acre watershed located in Fort Collins, CO. The wetland has shown measurable pollutant removal with its current outlet design, but the pollutant removal efficiency could be increased through the installation of a water quality control structure (WQCS). The wetland is bounded by an adjacent park, stream, bike path, and building limiting water quality improvement options. Thus, the wetland dimensions cannot be altered. The objective of this project is to design a water quality control structure that would maximize pollutant removal efficiency and the mass of total suspended solids (TSS) removed in the wetland without causing additional flooding at the site and adversely affecting the adjacent properties. An additional objective of this project was to develop a method to calculate the hydraulic retention time (HRT) for a stormwater wetland. EPA's Stormwater Management Model Version 5 was used to model the existing conditions and various proposed WQCS drawdown times. The modeled drawdown times ranged from 2 hours to 72 hours. Continuous simulation modeling was used because the wetland volume could not be adjusted to contain the water quality capture volume. It was assumed that all stormwater runoff entering the wetland was captured and treated. Using the model generated volume, depth, and flow data, the non-steady state hydraulic retention times and hydraulic loading rates (HLR) were calculated for each drawdown time analyzed. The k-C* method developed by Kadlec and Knight (1996) and measured data from the wetland were used to calculate the pollutant removal efficiency and the total annual TSS removed. The results indicate that a drawdown time of 30 hours will provide the best removal efficiency while considering the site constraints. The installation of the WQCS will have an HRT of approximately 14 hrs and increase the removal efficiency by 14.2% and the total annual TSS removed by 31,100 lbs from existing conditions. Furthermore, the addition of the WCQS will only increase the maximum flooding depth and duration at the overflow locations by a maximum of 0.02 ft and 0.2 hrs, respectively, for the 100yr storm event. For the 2yr storm event, the addition of the WCQS will only increase the maximum flooding depth and duration at the overflow locations by a maximum of 0.01 ft and 0.1 hrs, respectively. The depth of water in the wetland, for both storm events analyzed, will not exceed the wetlands embankment at any location besides the overflow locations. At brimful conditions, the detained runoff water remains in the main channel and permanent pool areas of the wetland. The methods developed in this project can be used to retrofit an existing wetland with a WQCS that would maximize removal efficiency while considering site constraints.
Keywords: stormwater management; removal efficiency; stormwater quality control structure; hydraulic retention time; retrofit BMP